Comparative Study on Expert Witnesses in Court Proceedings - World Bank (World Bank, 2012)
The Turkish Ministry of Justice has identified the existing system of expert witnesses as an obstacle to the efficiency and effectiveness of the judicial services. The 2009 judicial reform strategy and the judicial reform action plan call for a comparative study analyzing the experience in other countries to provide input into the policy debate in Turkey. This study provides descriptions and analyses of approaches to the use of expert opinions in civil, criminal, and administrative court proceedings in France, Germany, Italy, and the United States. It focuses on five key areas: access to the function of expert, execution of an expert opinion, the opinion and its use in evidence, remuneration, and liability.